ANALISIS PENGARUH NILAI DAN RATING SUKUK TERHADAP RETURN SAHAM: PENDEKATAN EMPIRIS PADA EMITEN MANUFAKTUR DI BEI 2020–2024 - Dini Lestary; Fachrurazi; Fitri Jayanti; Miftah Nur Rasidin (Jurnal Keuangan dan Perbankan Syariah, 2025)
Purpose: This study aims to find out how the influence of the value of sharia bond issuance and the rating of sharia bond issuance on stock returns. Design/methodology/approach: The population in this study is manufacturing companies that issue sharia bonds and are listed on the Indonesia Stock Exchange in 2020-2024. The sample selection in this study used purposive sampling. Based on the criteria in the sample selection, 45 sharia bond issuances were obtained from 9 manufacturing companies that issued sukuk on the Indonesia Stock Exchange as the final sample. Data collection is obtained from the annual report and the company's website is then analyzed by multiple regression analysis of panel data. Research Findings: The results of this study show that from the results of the calculation of the value variable and the issuance rating affect the stock return, and the results of the calculation test get a significant value of 0.021881 less than 0.05, so it is understood that the variable and the issuance rating have an effect on the stock return as well as the result of the determination coefficient where the adjusted R-squared value of 87.5306% shows that the independent variable is able to explain the independent variable, namely the stock return. Contribution/Originality/Novelty: the variable and the issuance rating have an effect on the stock return as well as the result of the determination coefficient where the adjusted R-squared value of 87.5306% shows that the independent variable is able to explain the independent variable, namely the stock return.